Manajemen Pembelajaran Chromebook dalam Meningkatkan Prestasi Siswa di SMP Ma’arif Kraksaan - Rohmah, Siti; Izzah, Ismatul; Retna Yunita, Arifia (Indonesian Journal of Islamic Educational Management, 2024)
This research wants to explain how Chromebook learning management improves student learning achievement at Ma'arif Kraksaan Middle School. The aim of this research is to provide information regarding planning, implementation and evaluation of learning to improve student learning achievement using Chromebook media. The theory used in this data analysis is the Huberman & Miles theory which uses the method of drawing conclusions and presenting data. Qualitative methods were used in this research. The informants for this research consisted of school principals and teachers who were teaching staff at Ma'arif Kraksaan Middle School. The data collection method uses interviews, observation and document analysis to obtain valid data about Chromebook learning management to improve student achievement at Ma'arif Kraksaan Middle School. The results obtained are that students' level of understanding continues to increase regarding Chromebook devices as a learning medium at Ma'arif Kraksaan Middle School. From this level of understanding, it can improve student learning achievement in class.